The prevalence and dynamic balance ability of long-distance Kenyan runners with Achilles Tendinopathy - Chebet, H. Y.; Olivier, B.; Karuguti, M. W.; Opondo, E. (African Journal for Physical Activity and Health Sciences, 2021)
Achilles Tendinopathy (AT) can cause disability among athletes involved in running events and often leads to an early exit from a sporting career. AT has been associated with intense, prolonged, and repetitive functional demands exerted on the achilles tendon. It is thought to affect the athlete`s dynamic balance ability and performance. A cross-sectional study was conducted in high altitude training camps among long-distance Kenyan runners (N=410) to examine the prevalence of this musculoskeletal dysfunction and the runners` dynamic balance ability as measured using the Star Excursion Balance Test (SEBT). The prevalence of AT among the long-distance runners was 13.9% (n=57), comprising 42 men (73.7%) and 15 women (26.3%), with a median age of 27 years. A total of 61.4% (n=35) of the runners covered on average 151- 200 km per week. The mean weekly training mileage was 170.0 km with an average pace of 3.3 minutes per kilometer. The mean composite SEBT scores for the dominant and non-dominant legs were 81.85 and 82.42%, respectively. The average normalised reach distances on SEBT were 72.9%, 84.3%, and 89.2% for anterior, posterolateral, and posteromedial directions, respectively. There were statistically significant mean differences in scores between male and female runners, with these being higher in males compared to females (p < 0.05). A total of 91.23% (n=52) and 82% (n=47) of the runners with AT respectively had impaired balance on dominant and non-dominant legs of below 94%, and were therefore at risk of re-injury. There appear to be gender-based differences in the Kenyan athletes` SEBT scores, hence the need for gender specific SEBT scores.